2017
DOI: 10.12788/jhm.2768
|View full text |Cite
|
Sign up to set email alerts
|

Hospital‐Level Factors Associated with Pediatric Emergency Department Return Visits

Abstract: RV rates were associated with population social determinants of health and inversely related to staffing. Hospital-level variation may indicate population-level economic factors outside the control of the hospital and unrelated to quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…We report similar ED revisit rates as in the pediatric emergency medicine literature. 28,37,38,40,44 Although previous studies have examined predictors for pediatric ED revisits, 27,29,32,[36][37][38]40,[42][43][44] there are limited studies analyzing the impact of language. These focus on revisit to hospitalization and specific diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We report similar ED revisit rates as in the pediatric emergency medicine literature. 28,37,38,40,44 Although previous studies have examined predictors for pediatric ED revisits, 27,29,32,[36][37][38]40,[42][43][44] there are limited studies analyzing the impact of language. These focus on revisit to hospitalization and specific diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 ED revisits resulting in hospitalization are not necessarily associated with poorer quality care or medical errors [26][27][28] ; however, revisits overall may be associated with crowding, higher medical costs, and lower patient/family satisfaction. 24,[29][30][31][32] Pediatric ED return visits are widely studied, 26,27,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] but few studies examining revisit predictors include language as a factor. 13,14,39 A better understanding of the impact of language on pediatric care quality and outcomes 3 and improved solutions to address these disparities are needed.…”
Section: Introductionmentioning
confidence: 99%
“…An inverse relationship between socioeconomic status and risk of readmission has been described in other pediatric disease groups as well. [10][11][12] In a study of hospital-level factors associated with return visit rates and return visits with admission, Pittsenbarger et al 13 found that hospitals with the highest rates of these outcomes were more likely to serve populations with lower median household incomes. Proposed factors contributing to this relationship may include lack of access to outpatient follow-up leading to delays in care and therefore presentation with more severe illness.…”
Section: Discussionmentioning
confidence: 99%
“…This explanation may be further supported by our finding that many postdischarge ED visits are for conditions that are associated with discretionary hospitalization in the ED 27 . A third explanation for this finding may be that poor access to outpatient care outside the hospital setting results in higher postdischarge ED visit rates without increasing the acuity of these revisits or increasing readmission rates 28 ; however, given the validated, risk‐standardized approach to readmission measurement, this is unlikely. This is also unlikely given recent work by Sabbatini et al 23 demonstrating substantial acuity among patients who return to the ED following hospital discharge.…”
Section: Discussionmentioning
confidence: 99%